The genotypic identification of colicins produced by clinical isolates of Escherichia coli in Iraq (World Journal of Experimental Biosciences, 2015)
Escherichia coli is natural and essential part of the bacterial flora in the gut of humans and animals. E. coli produces colicin, proteinaceous toxin that could inhibit the growth of similar or closely related bacterial strains. The production incidence of four colicin types in E. coli were tested in 31 bacterial isolates isolated from different sources (urine, stool, blood, ear swab and sewage water) by using polymerase chain reaction of specific primer for each colicin type. Production of colicin E1 was detected in four bacterial isolates (13.33%), three of them isolated from urine samples, while the last isolated from sewage water. Colicin M was detected in 15 colicinogenic isolates (50%), 12 isolates isolated from urine, 2 from sewage, while last one from stool. However, colicin E3 and E9 were not detected in all colicinogenic isolates. E. coli isolated from human urinary tract infections showed high incidence of colicin M and E1 production, respectively